Pengembangan Aplikasi Mobile dengan Qt Sdk: Studi Kasus Monitoring Ruangan Menggunakan Kamera - Yansen Yansen; Agus Prijono (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Nowadays, cell phones or mobile phones have become a multipurpose tool. The developers of mobile phone/smartphone have added an assortment of features and applications that are very useful for the users. Nokia provides the opportunity for application developers by providing developers such as Qt SDK. Application developers can use Qt SDK to design and create applications that can run on mobile phones based on Symbian. In this research Qt SDK was used to create applications for monitoring a room using a camera and display it on a Symbian-based smartphone. Research also used webcam7 software to monitor the camera and display it on PC screen. The Symbian used was Nokia E71. The camera used webcam M-Tech camera connected to the PC via USB cable, and internal webcam. Virtual routers were used to make the laptop into an access point. Virtual routers created using the netsh command was typed at the command prompt laptop. Symbian smartphone was connected to the wifi on the laptop. By accessing the IP of the laptop, display on a webcam has successfully been seen through a symbian smartphone monitoring application created using Qt SDK.